Nanoplasma dynamics of single large xenon clusters irradiated with superintense x-ray pulses from the linac coherent light source free-electron laser - Gorkhover, Taisia; Epp, Sascha W.; Erk, Benjamin Michael Dieter; Foucar, Lutz Michael; Rolles, Daniel; Rudek, Benedikt; Rudenko, Artem; Schlichting, Ilme; Ullrich, Joachim (Physical review letters, 2012)
The plasma dynamics of single mesoscopic Xe particles irradiated with intense femtosecond x-ray pulses exceeding 1016 W/cm2 from the Linac Coherent Light Source free-electron laser are investigated. Simultaneous recording of diffraction patterns and ion spectra allows eliminating the influence of the laser focal volume intensity and particle size distribution. The data show that for clusters illuminated with intense x-ray pulses, highly charged ionization fragments in a narrow distribution are created and that the nanoplasma recombination is efficiently suppressed.